2007
DOI: 10.1016/j.ejca.2007.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Membrane type matrix metalloproteinases (MMPs) show differential expression in non-small cell lung cancer (NSCLC) compared to normal lung: Correlation of MMP-14 mRNA expression and proteolytic activity

Abstract: Bradford Scholars -how to deposit your paper Overview Copyright check• Check if your publisher allows submission to a repository.• Use the Sherpa RoMEO database if you are not sure about your publisher's position or email openaccess@bradford.ac.uk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
37
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 28 publications
5
37
0
1
Order By: Relevance
“…However, MT1-MMP does not require additional activation, due to its capacity to be presented on the cell membrane in its active form [34]. MT1-MMP is an essential pericellular collagenolytic enzyme during tumor growth, angiogenesis, and invasion [35]. The overexpression of MT1-MMP was observed in human lung cancer, colon cancer, breast cancer, prostate cancer, and glioblastomas compared with benign tumor or normal tissue [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…However, MT1-MMP does not require additional activation, due to its capacity to be presented on the cell membrane in its active form [34]. MT1-MMP is an essential pericellular collagenolytic enzyme during tumor growth, angiogenesis, and invasion [35]. The overexpression of MT1-MMP was observed in human lung cancer, colon cancer, breast cancer, prostate cancer, and glioblastomas compared with benign tumor or normal tissue [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are an important part of these proteolytic enzymes [39]. They are highly expressed in multiple malignancies, including breast cancer [40], ovarian cancer [41], lung cancer [42] and colon cancer [43]. In addition, it has been reported that blockade of the expression and activity of MMPs could be the major cause of reduced motility and metastasis of cancer cells [44].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs such as interstitial collagenase (MMP-1) and type IV collagenases (MMP-2, MMP-9) are involved in the initial breakdown of collagen and basement membrane components during tumor growth and invasion. Overexpression of MMP-1, MMP-2 and MMP-9, MMP-11, MMP-13, MMP-14-17, MMP-24 and MMP-25, and TIMP-1 and TIMP-2 positively correlated with more advanced-stage disease and highly invasive and meta-static potential of carcinomas [7,8,9]. …”
Section: Discussionmentioning
confidence: 99%